2017
DOI: 10.1007/s12094-017-1639-9
|View full text |Cite
|
Sign up to set email alerts
|

The expression of HDAC7 in cancerous gastric tissues is positively associated with distant metastasis and poor patient prognosis

Abstract: These results indicate that high HDAC7 expression in cancerous gastric tissues correlates with distant metastasis and predicts a poor prognosis for patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…Moreover, our results indicated that HDAC7 is necessary and sufficient to maintain the CSC phenotype in these cells [1]. Independently, studies from several laboratories showed that HDAC7 expression correlates with poor patient outcome, drug resistance, and metastasis in ovarian, gastric, lung, colon, and salivary cancers [19][20][21][22][23][24]. Interestingly, HDAC7 is the only HDAC family member that is degraded by all HDAC inhibitors tested, suggesting that it may be a point of convergence of HDAC inhibition [1,27,28,38].…”
Section: Activation Of Transcription By Hdacsmentioning
confidence: 56%
See 2 more Smart Citations
“…Moreover, our results indicated that HDAC7 is necessary and sufficient to maintain the CSC phenotype in these cells [1]. Independently, studies from several laboratories showed that HDAC7 expression correlates with poor patient outcome, drug resistance, and metastasis in ovarian, gastric, lung, colon, and salivary cancers [19][20][21][22][23][24]. Interestingly, HDAC7 is the only HDAC family member that is degraded by all HDAC inhibitors tested, suggesting that it may be a point of convergence of HDAC inhibition [1,27,28,38].…”
Section: Activation Of Transcription By Hdacsmentioning
confidence: 56%
“…At least in the case of breast CSCs HDAC7 seems to play a critical role in regulating a differentiation program involving many oncogenes and stem cell transcription factors. It is possible that other HDACs may play a similar role in other tissue types, also HDAC7 may be involved in other tumors, as suggested by recent studies in ovarian, gastric, lung, colon, and salivary cancers [19][20][21][22][23][24].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, Peixoto P et al found that inhibiting HDAC7 reduced the tumorigenic activity of human glioblastoma and provided a new opportunity for tumor treatment [27]. Yu Y et al have shown that high HDAC7 expression in cancerous gastric tissues correlates with distant metastasis and predicts a poor prognosis for patients with gastric cancer [28]. However, the Fig.…”
Section: Discussionmentioning
confidence: 99%
“…HDAC7 regulates cell proliferation, differentiation, apoptosis, migration, and stemness in the physiological and pathological condition 12 . Aberrant expression of HDAC7 has been observed in the lung 13,14 , gastric 15 , breast 16,17 , and ovarian cancer 17 , glioma 18 , and hemolymphatic tumors 19,20 . High HDAC7 expression is correlated with metastasis and poor prognosis 13,15,20 .…”
Section: Introductionmentioning
confidence: 99%